2021
DOI: 10.1097/rmr.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection for Transoral Robotic Surgery (TORS) in Oropharyngeal Squamous Cell Carcinoma

Abstract: Transoral robotic surgery (TORS) is an excellent treatment strategy for well-selected patients with oropharyngeal squamous cell carcinoma. Potential benefits of TORS are greatest among patients for whom surgical resection will reduce or eliminate the need for adjuvant therapy. Proper patient selection largely depends on imaging, which is used to determine tumor resectability, to inform expected morbidity and functional outcome, to assess the potential need for adjuvant therapy, to evaluate for vascular or othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…While TOS can be applied to advanced T-stage oropharyngeal tumors, even at the most experienced centers over 90% of cases are T1-2 (12). Even within early stage tumors, candidates for TOS are carefully selected based on anatomical tumor limits similar to those used in our study, limited comorbidities, lack of trismus and adequate neck dissection as described by many authors (13)(14)(15)(16)). This selection of lower volume, more super cial tumors without obviously ECE imparts a signi cant potential bias.…”
Section: Discussionmentioning
confidence: 98%
“…While TOS can be applied to advanced T-stage oropharyngeal tumors, even at the most experienced centers over 90% of cases are T1-2 (12). Even within early stage tumors, candidates for TOS are carefully selected based on anatomical tumor limits similar to those used in our study, limited comorbidities, lack of trismus and adequate neck dissection as described by many authors (13)(14)(15)(16)). This selection of lower volume, more super cial tumors without obviously ECE imparts a signi cant potential bias.…”
Section: Discussionmentioning
confidence: 98%
“…As treatment approaches have evolved in the management of oropharyngeal squamous cell carcinoma (OPSCC), a major focus of treatment counseling has been toward the mitigation of functional adverse outcomes. In select patients, surgical management of OPSCC with or without adjuvant therapy offers equivalent oncologic outcomes to definitive radiation therapy with or without chemotherapy . Careful patient selection for each approach is needed for optimal speech and swallow outcomes, recognizing choice of treatment is rarely unequivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Careful patient selection for each approach is needed for optimal speech and swallow outcomes, recognizing choice of treatment is rarely unequivocal. Additionally, the younger and healthier demographic of patients with HPV-associated OPSCC may raise the incidence of delayed treatment complications . The phase 2 randomized treatment deintensification trial, ECOG-ACRIN 3311, involving patients with p16 positive OPSCC recently reported a greater than 90% 2-year progression-free survival (PFS) in all treatment groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te other limitations included the 2dimensional cutting plane, serious thermal damage, and the risk of a catastrophic laser fre [12,13]. TORS is another minimally invasive procedure that was approved by the FDA for treating early-stage OPSCC in 2009, with excellent visualization, decreased line of sight issues (using a 30 °endoscope), improved range of motion (360 °robotic arm movement), precise cutting, and easier en bloc resection [14][15][16][17][18][19][20]. Nevertheless, it lacks haptic feedback, and it is hard to popularize due to its extremely high cost of purchase and maintenance.…”
Section: Introductionmentioning
confidence: 99%